Effects of Natural Fillers in Wheat on Broiler Growth Performance - Sultana, Fowzia; Howlider, Muhammad Abdur Rahman (International Journal of Poultry Science, 2008)
A total of 180 day-old straight run arbor acres broiler chicks were fed ad libitum on 5 iso nitrogenous (starter, 22-23; finisher, 20-21) and iso energetic (starter, 2900-3000; finisher, 3100-3200) diets containing different levels of filler such as, D0 (100% filler), D1 (75% filler), D2 (50% filler), D3 (25% filler), D4 (0% filler) for a period of 42 days. Decreasing fillers from dietary wheat increased crude protein decreased crude fibre and ME content of wheat and diet. Decreasing filler in wheat increased live weight and improved conversion leading to higher profitability. It is concluded that removal of fillers may be beneficial in improving growth performance and profitability of broiler rearing.